2003
DOI: 10.1242/dev.00652
|View full text |Cite
|
Sign up to set email alerts
|

A Twist-like bHLH gene is a downstream factor of an endogenous FGF and determines mesenchymal fate in the ascidian embryos

Abstract: Ascidian larvae develop mesenchyme cells in their trunk. A fibroblast growth factor (FGF9/16/20) is essential and sufficient for induction of the mesenchyme in Ciona savignyi. We have identified two basic helix-loop-helix (bHLH) genes named Twist-like1 and Twist-like2 as downstream factors of this FGF. These two genes are phylogenetically closely related to each other, and were expressed specifically in the mesenchymal cells after the 110-cell stage. Gene-knockdown experiments using a specific morpholino oligo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 31 publications
1
79
0
Order By: Relevance
“…The scope of FGF pathway members has been investigated in lower chordates that diversified before vertebrate genome duplications, and this has provided a clearer picture of FGF family evolution within the deuterostomes. In the urochordate ascidians Ciona intestinalis and Ciona savigny (whose genomes have been sequenced) there are six FGF ligands and one FGF receptor (Imai et al , 2003.…”
Section: Fgf Signaling Complexity In the Metazoamentioning
confidence: 99%
“…The scope of FGF pathway members has been investigated in lower chordates that diversified before vertebrate genome duplications, and this has provided a clearer picture of FGF family evolution within the deuterostomes. In the urochordate ascidians Ciona intestinalis and Ciona savigny (whose genomes have been sequenced) there are six FGF ligands and one FGF receptor (Imai et al , 2003.…”
Section: Fgf Signaling Complexity In the Metazoamentioning
confidence: 99%
“…Two bHLH transcription factor genes, Twist-like1 and Twist-like2, have been shown to be involved in mesenchyme formation in C. savignyi (Imai et al, 2003). Cs-Twist-like1 is upstream of Cs-Twist-like2, as well as of the homeobox gene Cs-Hex, the gene Cs-Mist, encoding a bHLH transcription factor, and the mesenchymespecific gene Cs-Mech.…”
Section: Mesenchymementioning
confidence: 99%
“…Cs-Twist-like1 is upstream of Cs-Twist-like2, as well as of the homeobox gene Cs-Hex, the gene Cs-Mist, encoding a bHLH transcription factor, and the mesenchymespecific gene Cs-Mech. Overexpression and morpholino knockdown experiments have demonstrated that CsTwist-like1 is necessary and sufficient for mesenchyme differentiation (Imai et al, 2003).…”
Section: Mesenchymementioning
confidence: 99%
“…servation with the vertebrate Hand genes, whereas Ci-Hndx is quite divergent (16). Nonetheless, Ci-Hndx is expressed in the TVCs at the tailbud stage [along with transient expression in the trunk lateral cells and endoderm at earlier stages, (19), referred to as Ci-NoTrlc]. Given the overlapping expression of Ci-NPP and Ci-Hndx in the TVCs and endoderm, bioinformatics methods were used to identify shared sequence motifs within their 5Ј flanking regions.…”
Section: G H and M)mentioning
confidence: 99%